Cardiac Dysfunction and Arrhythmias 3 Months After Hospitalization for COVID‐19 - Charlotte B. Ingul; Jostein Grimsmo; Albulena Mecinaj; Divna Trebinjac; Magnus Berger Nossen; Simon Andrup; Bjørnar Grenne; Håvard Dalen; Gunnar Einvik; Knut Stavem; Turid Follestad; Tony Josefsen; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background The extent of cardiac dysfunction post‐COVID‐19 varies, and there is a lack of data on arrhythmic burden. Methods and Results This was a combined multicenter prospective cohort study and cross‐sectional case‐control study. Cardiac function assessed by echocardiography in patients with COVID‐19 3 to 4 months after hospital discharge was compared with matched controls. The 24‐hour ECGs were recorded in patients with COVID‐19. A total of 204 patients with COVID‐19 consented to participate (mean age, 58.5 years; 44% women), and 204 controls were included (mean age, 58.4 years; 44% women). Patients with COVID‐19 had worse right ventricle free wall longitudinal strain (adjusted estimated mean difference, 1.5 percentage points; 95% CI, −2.6 to −0.5; P=0.005) and lower tricuspid annular plane systolic excursion (−0.10 cm; 95% CI, −0.14 to −0.05; P<0.001) and cardiac index (−0.26 L/min per m2; 95% CI, −0.40 to −0.12; P<0.001), but slightly better left ventricle global strain (−0.8 percentage points; 95% CI, 0.2–1.3; P=0.008) compared with controls. Reduced diastolic function was twice as common compared with controls (60 [30%] versus 29 [15%], respectively; odds ratio, 2.4; P=0.001). Having dyspnea or fatigue were not associated with cardiac function. Right ventricle free wall longitudinal strain was worse after intensive care treatment. Arrhythmias were found in 27% of the patients, mainly premature ventricular contractions and nonsustained ventricular tachycardia (18% and 5%, respectively). Conclusions At 3 months after hospital discharge with COVID‐19, right ventricular function was mildly impaired, and diastolic dysfunction was twice as common compared with controls. There was little evidence for an association between cardiac function and intensive care treatment, dyspnea, or fatigue. Ventricular arrhythmias were common, but the clinical importance is unknown. Registration URL: http://clinicaltrials.gov. Unique Identifier: NCT04535154.